Can computed tomodensitometry predict ventricular pseudoaneurysm occurrence after heart valve endocarditis?. (22nd August 2019) - Fouilloux, Virginie; Aldebert, Philippe; Gorincour, Guillaume
Abstract: Ventricular pseudoaneurysm is a rare but well-known complication after valvular endocarditis. The lesion was localised exactly where pre-operative CT scan showed lack of enhancement in the postero-lateral wall of the left ventricle. This case demonstrates how much attention must be paid to myocardial CT images and emphazises the need of close follow-up in patients with infective endocartitis.